A study on the effectiveness of HRM practices and how it helps to resolve the internal worker disputes of DKL Ltd; Epyllion Group - Farah, Rukaiya Ahsan (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.